Polymorphic variants of GSTM1, GSTT1, and GSTP1 genes in childhood acute leukemias: A preliminary study in Argentina - Weich, Natalia (2015)
Background and Aim Despite recent major advances in leukemia research, the etiopathogenesis of childhood leukemias remains far elusive. Individual predisposing factors, including polymorphisms in detoxification enzymes, have been implicated in the molecular pathogenesis and heterogeneity of the disease. Genetic polymorphisms of glutathione S-transferases (GSTs) that alter enzyme activity could be an additional factor that increases the risk of acute leukemia, but data are lacking in Argentina. We assessed the association of GST polymorphisms and the susceptibility to childhood leukemia in Argentina by conducting an exploratory case-control study and correlated patients´ genotype to clinical and biological features. Methods Deletion polymorphisms in GSTM1 and GSTT1 genes and the single nucleotide polymorphism in GSTP1 c.319A>G (rs1695; p.105Ile>Val) were genotyped by PCR methods in 36 patients and 133 healthy individuals. Results GSTM1-null genotype was associated with a lower risk of developing acute leukemia (P = 0.013; OR: 0.31; CI: 0.12-0.80), while GSTP1-GG variants displayed an increased risk (P = 0.01; OR: 3.9; CI: 1.85-8.2). However, no differences were found for GSTT1 gene. Conclusion These preliminary results, to be validated in a larger population from Argentina, suggest that the development of pediatric leukemia may be differentially influenced by genotypic variants in GST genes.